2018
DOI: 10.1002/er.4330
|View full text |Cite
|
Sign up to set email alerts
|

A price-regulated electric vehicle charge-discharge strategy for G2V, V2H, and V2G

Abstract: Summary Electric vehicles (EVs) and smart grids are gradually revolutionising the transportation sector and electricity sector respectively. In contrast to unplanned charging/discharging, smart use of EV in home energy management system (HEMS) can ensure economic benefit to the EV owner. Therefore, this paper has proposed a new energy pricing controlled EV charging/discharging strategy in HEMS to acquire maximum financial benefit. EV is scheduled to be charged/discharged according to the price of electricity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 24 publications
(37 reference statements)
0
33
0
Order By: Relevance
“…The emerging home automation management privileges the customers to drop the consumptions at high prices and manage the concerned electric devices conferring to user priority and on‐line grid situation . In Reference the researchers proposed a price‐controlled strategy for charging and discharging EVs in‐home energy management systems to get maximum economic benefit in Australia. The EVs participating in V2H during peak energy pricing periods contribute an 11.6% reduction in the daily and monthly cost as compared with the grid to vehicle (G2V) operation mode.…”
Section: Interaction Of Ev In Smart Grid Environmentmentioning
confidence: 99%
“…The emerging home automation management privileges the customers to drop the consumptions at high prices and manage the concerned electric devices conferring to user priority and on‐line grid situation . In Reference the researchers proposed a price‐controlled strategy for charging and discharging EVs in‐home energy management systems to get maximum economic benefit in Australia. The EVs participating in V2H during peak energy pricing periods contribute an 11.6% reduction in the daily and monthly cost as compared with the grid to vehicle (G2V) operation mode.…”
Section: Interaction Of Ev In Smart Grid Environmentmentioning
confidence: 99%
“…Nevertheless, in order to participate in providing ancillary services, an efficient charging/discharging strategy for EV must be considered. Regardless of operation modes, smart energy management of EV can ensure reduced energy consumption from the grid and thus provide direct economic benefit to the customers [20].…”
Section: Introductionmentioning
confidence: 99%
“…The RTP rate varies hourly whereas the TOU rate is adjusted by blocks of time during the day (generally three blocks, that is, peak, shoulder or intermediate peak, and off‐peak) . The TOU pricing tariff is a commonly used dynamic tariff mechanism whilst the RTP pricing tariff is a more complex instrument and presents higher efficiency gains in comparison to TOU mechanism …”
Section: Introductionmentioning
confidence: 99%
“…11 The TOU pricing tariff is a commonly used dynamic tariff mechanism whilst the RTP pricing tariff is a more complex instrument and presents higher efficiency gains in comparison to TOU mechanism. 12 Many previous studies have observed the impacts of EV charging on electric power systems. For instance, Akhavan-Rezai et al 13 propose a method of analyzing the impacts of EV plug-in hybrids uncoordinated charging on a local existent distribution network in Canada.…”
Section: Introductionmentioning
confidence: 99%